Decolonizing Management and Leading Change through African Philosophy (Glocalism: Journal of Culture, Politics and Innovation, 2021)
Africa currently operates and manages her affairs with and from a colonial perspective, in business, politics, and education. Living everyday life through a colonial lens has stunted growth and innovation because instead of using her strengths, which is leading with African management philosophy, Africa continues to operate with a Western framework, that is a system where the toxic influence and effects of coloniality continues to permeate African political institutions, the education system and culture. The authors advocate for a return to indigenous management philosophy, to ensure success and long-term sustainability. This paper sheds light on a historical background of African societies prior to the destruction of her cultures and institutions by slavery and colonialism. The authors offer key differences between African and Western approaches to show why the Western system has failed Africa. Lastly, the authors offer a framework for policy formulation in the form of propositions.
Keywords: African philosophy; leadership; colonialism; decolonization; management